1982
DOI: 10.1159/000233177
|View full text |Cite
|
Sign up to set email alerts
|

FcIgG Receptor-Bearing Lymphocytes and Monoclonal Antibody-Defined T Cell Subsets in Atopic Dermatitis: Effect of Treatment with Thymopoietin Pentapeptide (TP-5)

Abstract: Lymphocyte subpopulations were determined in the blood of patients with atopic dermatitis (AD) before and after treatment with the thymopoietin pentapeptide TP-5. The relative and absolute numbers of lymphocytes bearing suppressor/cytotoxic cell markers (FcIgG+E+ and T8+ cells) were significantly decreased in the untreated patients and the T4+/T8+ cell ratio was increased, indicating an imbalance between lymphocyte subpopulations in AD. Patients who had be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Furthermore, successful hyposensitisation treat ment may be accompanied by alterations in T cell populations [7], correcting the abnormal helper/suppressor T cell ratio observed in atopic individuals [23]. Immunotherapy with appropriately modified aller gens may additionally, therefore, bring about benefi cial changes in regulatory T cell function, although the design and evaluation of such therapeutic materi als still remain empirical.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, successful hyposensitisation treat ment may be accompanied by alterations in T cell populations [7], correcting the abnormal helper/suppressor T cell ratio observed in atopic individuals [23]. Immunotherapy with appropriately modified aller gens may additionally, therefore, bring about benefi cial changes in regulatory T cell function, although the design and evaluation of such therapeutic materi als still remain empirical.…”
Section: Discussionmentioning
confidence: 99%
“…Tt was originally thought that these surface markers functionally separated these sub-populations into suppressor and helper cells, respectively [22]. Several investigators reported decreased numbers of T gamma cells in patients with atopic dermatitis [23,24] or severe respiratory allergy (25). The degree of reduction in the T gamma cell population appeared to correlate with disease activity.…”
Section: Ptienotypic Studies Of T Cell Subsets In Atopic Diseasesmentioning
confidence: 99%
“…Many studies measuring circulating T lymphocyte subsets in patients with atopic dermatitis have reported an increased helper/suppressor (OKT 4/OKT 8) ratio [24,[26][27][28]. This increase was the result of a lowered OKT 8 percentage in three studies [26][27][28], and increased OKT 4 percentage in another study [29].…”
Section: Ptienotypic Studies Of T Cell Subsets In Atopic Diseasesmentioning
confidence: 99%
“…Atopic infants have been reported to have a lower number of T lympho cytes [16,17], particularly of the suppressor type [18], but more helper cells [19] and an increased helper/ suppressor ratio [17,19,20], Infants with heredity for atopy had less T lymphocytes, counted as sheep eryth rocyte rosette-forming cells, at the age of 1 month, than infants without such heredity [21]. Change in T lymphocyte function has been suggested to be the pri mary event leading to the increased IgE production typical of atopy [22], In this study, by contrast, infants with heredity for atopy had a similar number of T, T helper and T suppressor cells as those without atopic family members.…”
Section: Discussionmentioning
confidence: 99%